2020
DOI: 10.32345/2664-4738.1.2020.02
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific Immunity in Bacterial Dysbiosis and Bacterial Vaginosis

Abstract: Relevance. The state of dysbiosis and bacterial vaginosis (BV) is characterized by the formation of both systemic and local immune deficiency, which corresponds to the increase in the number of pathogenic microbiota. It is necessary to study the state of non-specific factors of cellular and humoral resistance in the development of bacterial dysbiosis and BV. Objectives – to determine the state of nonspecific immunity in bacterial dysbiosis and BV on CD16-cells, as well as indicators in the blood and vagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Our previous studies [17,18,21,22] showed that in dysbiosis on the background of general lymphocytosis there was a gradual, related to the increasing severity of dysbiosis, decrease in the content of CD3-and CD4-lymphocytes in blood, which was expressed to a In this work, we focus on identifying the interrelations between the immunological parameters studied and the PCR data with the estimation of the number of certain biocenosis indicators. Table 1 In normocenosis, NBI was determined by complement activation (component C4);…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous studies [17,18,21,22] showed that in dysbiosis on the background of general lymphocytosis there was a gradual, related to the increasing severity of dysbiosis, decrease in the content of CD3-and CD4-lymphocytes in blood, which was expressed to a In this work, we focus on identifying the interrelations between the immunological parameters studied and the PCR data with the estimation of the number of certain biocenosis indicators. Table 1 In normocenosis, NBI was determined by complement activation (component C4);…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown [17,22] According to the results obtained, dependence of key microbial factors on immune system indicators was analyzed (Table 3). Regression analysis was performed for all indicators, but only statistically significant ones (p <0.05) are presented in the Table3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Symbiotic microflora plays an important role in maintaining the colonization resistance of the vaginal biotopea complex, multicomponent and equilibrium-dynamic mechanism that ensures the stability of the population-quantitative composition of components of the normal biocenosis [7,16,18,21]. Modern ideas about the composition of vaginal biota are based primarily on the results of microscopic and microbiological examination of vaginal secretions, which have known drawbacks that limit the objectivity and reliability of data on all the participants of the biocenosis [1,2,3,15].…”
mentioning
confidence: 99%